Additional file 3 of Revisiting chloroplast genomic landscape and annotation towards comparative chloroplast genomes of Rhamnaceae - Kwanjeera Wanichthanarak; Intawat Nookaew; Phongthana Pasookhush; Thidathip Wongsurawat; Piroon Jenjaroenpun; Namkhang Leeratsuwan; Songsak Wattanachaisaereekul; Wonnop Visessanguan; Yongyut Sirivatanauksorn; Narong Nuntasaen; Chutima Kuhakarn; Vichai Reutrakul; et al. (My University, 2023)
Additional file 3: Table S5. Codon usage of 86 protein-coding genes of each chloroplast genome.
Keywords: Rhamnaceae; Genomics and Phylogenetic Studies